Cuestiones alrededor del tiempo y el espacio. Muros y canales en la cuenca alta de la quebrada Piedras Blancas (Antioquia, Colombia) (2012)
ABSTRACT: As a result of an investigation carried out near of Medellin city, in an area of 1 km2 , are recorded walls, canals and side cuts, which arranged, construction techniques and spatial relationships, associated with domestic, agricultural, mining and indeterminate activities, indicating unique spaces in the area and in the regional archaeological record. Concerns us provide the necessary information for their evaluation and analysis, in the light of the questions that suggest by the dating obtained.